Global Practice Patterns and Variations in the Medical and Surgical Management of Non- Obstructive Azoospermia: Results of a World-Wide Survey, Guidelines and Expert Recommendations - Amarnath Rambhatla; Rupin Shah; Imad Ziouziou; Priyank Kothari; Gianmaria Salvio; Murat Gul; Taha Hamoda; Parviz Kavoussi; Widi Atmoko; Tuncay Toprak; Ponco Birowo; Edmund Ko; et al. (The World Journal of Men's Health)
Purpose: Non-obstructive azoospermia (NOA) is a common, but complex problem, with multiple therapeutic options and a lack of clear guidelines. Hence, there is considerable controversy and marked variation in the management of NOA. This survey evaluates contemporary global practices related to medical and surgical management for patients with NOA. Materials and Methods: A 56-question online survey covering various aspects of the evaluation and management of NOA was sent to specialists around the globe. This paper analyzes the results of the second half of the survey dealing with the management of NOA. Results have been compared to current guidelines, and expert recommendations have been provided using a Delphi process. Results: Participants from 49 countries submitted 336 valid responses. Hormonal therapy for 3 to 6 months was suggested before surgical sperm retrieval (SSR) by 29.6% and 23.6% of participants for normogonadotropic hypogonadism and hypergonadotropic hypogonadism respectively. The SSR rate was reported as 50.0% by 26.0% to 50.0% of participants. Interestingly, 46.0% reported successful SSR in <10% of men with Klinefelter syndrome and 41.3% routinely recommended preimplantation genetic testing. Varicocele repair prior to SSR is recommended by 57.7%. Half of the respondents (57.4%) reported using ultrasound to identify the most vascularized areas in the testis for SSR. One-third proceed directly to microdissection testicular sperm extraction (mTESE) in every case of NOA while others use a staged approach. After a failed conventional TESE, 23.8% wait for 3 months, while 33.1% wait for 6 months before proceeding to mTESE. The cut-off of follicle-stimulating hormone for positive SSR was reported to be 12–19 IU/mL by 22.5% of participants and 20–40 IU/mL by 27.8%, while 31.8% reported no upper limit. Conclusions: This is the largest survey to date on the real-world medical and surgical management of NOA by reproductive experts. It demonstrates a diverse practice pattern and highlights the need for evidence-based international consensus guidelines.